Timing of active left ventricular unloading in patients on venoarterial extracorporeal membrane oxygenation therapy - Schrage, Benedikt; Sundermeyer, Jonas; Blankenberg, Stefan; Colson, Pascal; Eckner, Dennis; Eden, Matthias; Eitel, Ingo; Frank, Derk; Frey, Norbert; Graf, Tobias; Kirchhof, Paulus; Kupka, Danny; et al. (JACC Heart failure, 2023)
Background - It is currently unclear if active left ventricular (LV) unloading should be used as a primary treatment strategy or as a bailout in patients with cardiogenic shock (CS) treated with venoarterial extracorporeal membrane oxygenation (VA-ECMO). - Objectives - This study sought to evaluate the association between timing of active LV unloading and implantation of VA-ECMO with outcomes of patients with CS. - Methods - Data from 421 patients with CS treated with VA-ECMO and active LV unloading at 18 tertiary care centers in 4 countries were analyzed. Patients were stratified by timing of device implantation in early vs delayed active LV unloading (defined by implantation before up to 2 hours after VA-ECMO). Adjusted Cox and logistic regression models were fitted to evaluate the association between early active LV unloading and 30-day mortality as well as successful weaning from ventilation. - Results - Overall, 310 (73.6%) patients with CS were treated with early active LV unloading. Early active LV unloading was associated with a lower 30-day mortality risk (HR: 0.64; 95% CI: 0.46-0.88) and a higher likelihood of successful weaning from ventilation (OR: 2.17; 95% CI: 1.19-3.93) but not with more complications. Importantly, the relative mortality risk increased and the likelihood of successful weaning from ventilation decreased almost proportionally with the time interval between VA-ECMO implantation and (delayed) initiation of active LV unloading. - Conclusions - This exploratory study lends support to the use of early active LV unloading in CS patients on VA-ECMO, although the findings need to be validated in a randomized controlled trial.
Online veröffentlicht: 11. Januar 2023, Artikelversion: 6. März 2023
Gesehen am 04.09.2023